Ekplorasi Hubungan Return On Investment (ROI) dan Price to Book Value (PBV) di PT Indofood Sukses Makmur Tbk.: ROI, PBV, Profitability, Financial Performance - Dheri Febiyani Lestari; Alfin Nur Arifah; Rizky Ridwan; Aditia Abdurachman (EKOBIMA, 2024)
The purpose of this study is to examine the relationship between PT Indofood Sukses Makmur Tbk's profitability and the company's financial performance. To this end, financial data from PT Indofood Sukses Makmur Tbk was used to gather quantitative data from the population. Purposive sampling was used to obtain samples from the population, specifically the company's annual financial data for the years 2020–2023, and multiple linear regression was employed as the analysis method, with financial performance serving as the dividend variable and return on investment as the independent variable.The analysis of data using analysis of simple linear regression. According to research findings, corporate financial performance data (PBV) is 0.76, 0.64, 0.63, and 0.57, while profitability data (ROI) for the 2020–2023 period is 0.5, 0.6, 0.5, 0.6. According to the findings of the data analysis, the company's financial performance (PBV) was positively and significantly impacted by profitability (ROI). This demonstrates that PT Indofood Sukses Makmur Tbk may turn a profit over the 2020–2023 timeframe, which will help the business's long-term expansion and viability..